Participles in English to Sanskrit machine translation - Mishra V.; Mishra R.B. (My University, 2025)
In this paper, we discuss the participle type of English sentences in our English to Sanskrit machine translation (EST) system. Our EST system is an integrated model of a rule based machine translation (RBMT) with artificial neural network (ANN) model which translates an English sentence into equivalent Sanskrit sentence. We use feed forward ANN for the selection of Sanskrit word like noun, verb, object, adjective etc from English to Sanskrit user data vector (UDV). Our system uses only morphological markings to identify various part of speech (POS) as well as participle type of sentences. © 2011 Springer-Verlag.